Recent advances in encapsulation of drug delivery active substance in Cubosomes for skin diseases - Zakaria, Fazila; Ashari, Siti Efliza; Mat Azmi, Intan Diana; Abdul Rahman, Mohd Basyaruddin (Editions de Sante, 2022)
Over the past decade, topical drug delivery has received exceptional attention notably due to the rising skin-related diseases, greater call for an effective patient compliant and targeted delivery system, and growing interest in life cycle management strategies among pharmaceutical companies. Generally, a topical drug delivery system is a transport carrier or a chemical formulation that safely transports therapeutic agents at a controlled rate to achieve effective concentration to the specific body site. The amount of active substance must be sufficiently loaded into the carrier, which largely depends on the interaction of the vehicle and active to produce the maximum therapeutic effects. Recently, the introduction of cubosomes is regarded as a promising lipid-based nanosystem for the treatment of skin diseases. Cubosomes are a type of liquid crystalline nanoparticles developed mostly from amphiphilic lipids, particularly glyceryl monooleate or phytantriol with the addition of a suitable stabiliser. Their unique characteristics and high compatibility with various active substances allow for their broad applications, including oral, ocular, transdermal, and chemotherapy drug delivery. The extensive loading capacity of cubosomes with hydrophilic, lipophilic, and amphiphilic drug molecules also represents a novel and versatile drug delivery system. Therefore, this review summarised the latest development of cubosomes as a promising drug transport carrier for skin disease treatment. Various topics were highlighted and discussed, including the structure and unique properties of cubosomes, the available preparation methods, the characterisation approaches and the recently patented cubosomes. Furthermore, the application of encapsulated cubosomes with various active substances ranging from synthetic drugs to plant extract sources were presented.